THE INFLUENCE OF SERVICE QUALITY AND APPARATUS DISCIPLINE ON COMMUNITY SATISFACTION IN TUTULO VILLAGE, BOTUMOITO DISTRICT - Hadjatu, Sri; Mooduto, William Indra S; Wahdah, Ghoriqna Fibahril (Jurnal Ilmu Manajemen dan Bisnis, 2025)
This study aims to (1) determine the influence of service quality on community satisfaction in Tutulo Village, Botumoito District, (2) determine the influence of apparatus discipline on community satisfaction in Tutulo Village, Botumoito District, and (3) determine the influence of service quality and apparatus discipline on community satisfaction in Tutulo Village, Botumoito District.The method in this study uses a quantitative approach. The population amounts to 1,534 individuals. A sampling technique was used to select the samples. The sample in the study numbered 156. Data collection techniques were conducted through observation and questionnaires.The research results show that service quality (X1) has a positive and significant effect on public satisfaction (Y). From the testing, the t-test yielded a significance value of 0.005 (<0.05) and a t-value of 2.828 (>1.975). (2) Civil Servants' Discipline (X2) also has a positive and significant effect on public satisfaction (Y). The t-test results yielded a significance value of 0.008 (<0.05) and a t-value of 2.709 (>1.975). (3) Simultaneously, service quality and civil servants' discipline have a positive and significant effect on public satisfaction. From the F-test results, a significance value of 0.001 < 0.05 and an F-count value of 7.349 > F-table 2.06 were obtained.